2016
DOI: 10.1016/j.freeradbiomed.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of ascorbate and sorafenib in hepatocellular carcinoma: New insights into ascorbate cytotoxicity

Abstract: We investigated the mechanism of selective ascorbate-induced cytotoxicity in tumor cells, including Hep G2 cells, compared to primary hepatocytes. H2O2 formation was required for ascorbate cytotoxicity, as extracellular catalase treatment protected tumor cells. H2O2 generated by glucose oxidase treatment also caused cell killing, but treatment with a pharmacological dose (5-20 mM) of ascorbate was significantly more cytotoxic at comparable rates of H2O2 production, suggesting that ascorbate enhanced H2O2 cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…Previous studies have demonstrated that P-AscH − has synergistic or additive effects with many radio-chemotherapy regimens in cancer cells, and radio-protective effects in normal cells [17, 3842]. Our current study extends these observations to clearly demonstrate the efficacy of P-AscH − in the hypoxic environment of PDAC.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have demonstrated that P-AscH − has synergistic or additive effects with many radio-chemotherapy regimens in cancer cells, and radio-protective effects in normal cells [17, 3842]. Our current study extends these observations to clearly demonstrate the efficacy of P-AscH − in the hypoxic environment of PDAC.…”
Section: Discussionsupporting
confidence: 79%
“…25 , 26 We recently confirmed this previous work with a series of cell line experiments and also observed that ascorbate deregulates cellular calcium homeostasis, thereby promoting cell death. 27 There are also other proposed mechanisms of action. Ascorbate functions as a cofactor for a group of enzymes (Fe and 2-oxoglutarate-dependent dioxygenases) such as hypoxia inducible factor (HIF) hydroxylases, which affect HIF protein levels through marking HIF for proteosomal degradation and also cotranscription factor binding.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that have demonstrated a cytotoxic effect of ascorbate on tumor cells in vitro , either alone or in combination with chemotherapeutics ( Wells et al, 1995 ; Reddy et al, 2001 ; Pathak et al, 2002 ; Wozniak and Anuszewska, 2002 ; Guerriero et al, 2006 ; Kassouf et al, 2006 ; Chen et al, 2007 , 2012 ; Martinotti et al, 2011 ; Verrax et al, 2011 ; Ma et al, 2014 ; Cieslak et al, 2015 ; Xia et al, 2017 ) or radiation ( Herst et al, 2012 ; Castro et al, 2014 ). The cytotoxicity in many of these studies reflects the oxidative stress resulting from the H 2 O 2 generated in cell culture medium when ascorbate is present at concentrations of 1 mM or above, and manifests as increased cell cycle arrest, p53 upregulation, decreased ATP levels, compromised mitochondrial function, suppression of antioxidant gene expression NrF-2 and/or cell death by apoptosis ( Tarumoto et al, 2004 ; Fromberg et al, 2011 ; Rouleau et al, 2016 ; Yang et al, 2017 ). Anti-cancer effects have also been demonstrated with ascorbate levels well below 1 mM: levels as low as 100 μM or even 1 μM in the culture medium enhanced the susceptibility of cancer cells to etoposide, cisplatin, or doxorubicin ( Kurbacher et al, 1996 ; Reddy et al, 2001 ; Tarumoto et al, 2004 ; An et al, 2011 ).…”
Section: Anti-cancer Activities Of Ascorbatementioning
confidence: 99%